Biosensor based on tyrosinase immobilized on a single-walled carbon nanotube-modified glassy carbon electrode for detection of epinephrine - Apetrei IM (Dove Medical Press, 2013)
Irina Mirela Apetrei,1 Constantin Apetrei21Department of Pharmaceutical Sciences, Faculty of Medicine and Pharmacy, 2Department of Chemistry, Physics and Environment, Faculty of Sciences and Environment, Dunarea de Jos University of Galati, RomaniaAbstract: A biosensor comprising tyrosinase immobilized on a single-walled carbon nanotube-modified glassy carbon electrode has been developed. The sensitive element, ie, tyrosinase, was immobilized using a drop-and-dry method followed by cross-linking. Tyrosinase maintained high bioactivity on this nanomaterial, catalyzing the oxidation of epinephrine to epinephrine-quinone, which was electrochemically reduced (-0.07 V versus Ag/AgCl) on the biosensor surface. Under optimum conditions, the biosensor showed a linear response in the range of 10–110 µM. The limit of detection was calculated to be 2.54 µM with a correlation coefficient of 0.977. The repeatability, expressed as the relative standard deviation for five consecutive determinations of 10-5 M epinephrine solution was 3.4%. A good correlation was obtained between results obtained by the biosensor and those obtained by ultraviolet spectrophotometric methods.Keywords: amperometry, single-walled carbon nanotubes, spectrophotometry, catecholamine, pharmaceutical formula